2009
DOI: 10.2169/internalmedicine.48.2363
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies and Renal Outcomes in Patients with Lupus Nephritis

Abstract: Objective Previous studies have documented a high frequency of thrombotic events in lupus nephritis patients with antiphospholipid (aPL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…7 Among the predictive factors for development of CKD, eGFR at presentation and presence of hypertension were reported. 28 Of all our patients, 47.9% had hypertension. This is similar to the rate quoted for LN patients from the eastern region of Saudi Arabia (47%).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…7 Among the predictive factors for development of CKD, eGFR at presentation and presence of hypertension were reported. 28 Of all our patients, 47.9% had hypertension. This is similar to the rate quoted for LN patients from the eastern region of Saudi Arabia (47%).…”
Section: Discussionmentioning
confidence: 73%
“…19 A higher prevalence of 41% was reported from Japan. 28 In this paper, it was reported that the frequency of class V lupus nephritis was lower in aPL antibody-positive patients than in aPL antibody-negative patients. 28 We found no such association.…”
Section: Discussionmentioning
confidence: 84%
“…A variety of renal manifestations, including intra-glomerular capillary thrombosis and nephropathy, have been reported in APLa positive SLE patients. However, the true significance of APLa on the progression of lupus nephritis is still controversial [11], [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that the positive rate of aPL was 48.2% in patients with LN, which was higher or similar to that reported in previous studies of patients with SLE/LN. 1012 Given the high prevalence of aPL in patients with SLE, aPL may have some other clinical significance beyond thrombosis and pregnancy events. However, whether aPL are correlated with clinical activity, especially renal pathological activity in LN patients remains unclear.…”
Section: Discussionmentioning
confidence: 99%